CODIFYING GENDER COMMUNICATION: A QUASI-EXPERIMENTAL APPROACH TOWARDS IDENTIFYING DIFFERENCES IN EMOTIONAL EXPRESSIVITY - Raihan Muhammad, Athar; Dwiningtyas Sulistyani, Hapsari; Manalu, Rouli (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Two studies were conducted in order to contribute to diversifying the pillars of understanding on the interaction of gender to the concepts of emotional expression. Designed to understand both its key differences, this study utilizes a quasi-experimental method, with a mix of both controlled stimulant testings by an emotionally-inducing advertisement on populations of highly educated females and males. This study measures emotional expressivity in 6 dimensions, namely Sadness, Fear, Anger, Happiness, Surprise, and Disgusted, the results inhibit that the performative value of gender influences how emotional messages are captured.